1996
DOI: 10.1111/j.1365-2273.1996.tb01095.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of sleep nasendoscopy in the evaluation of patients with suspected sleep-related breathing disorders

Abstract: Fifty patients with sleep-related breathing disorders were tested with nocturnal polysomnography and with nasendoscopic diurnal polysomnography after diazepam administration, and various indices of breathing disorders were examined, and the results obtained in the two sleep studies compared. There were no significant differences between the two sleep studies in either the type of apnoea or the indices of breathing disorder except for the longest duration of apnoea. There was a significant difference in the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 9 publications
0
63
1
10
Order By: Relevance
“…First described as sleep nasendoscopy in 1991, 1 the technique requires pharmacologic sedation and fiberoptic visualization of the upper airway to observe directly and characterize the upper airway collapse that occurs during sedation. 2 Drug-induced sleep endoscopy has been shown to be a safe, feasible, and valid assessment of the upper airway, [3][4][5] and we have demonstrated moderate to substantial test-retest reliability. 6 The objective of this study was to examine DISE interrater reliability.…”
Section: Irway Obstruction Inmentioning
confidence: 94%
“…First described as sleep nasendoscopy in 1991, 1 the technique requires pharmacologic sedation and fiberoptic visualization of the upper airway to observe directly and characterize the upper airway collapse that occurs during sedation. 2 Drug-induced sleep endoscopy has been shown to be a safe, feasible, and valid assessment of the upper airway, [3][4][5] and we have demonstrated moderate to substantial test-retest reliability. 6 The objective of this study was to examine DISE interrater reliability.…”
Section: Irway Obstruction Inmentioning
confidence: 94%
“…DISE findings are reported using VOTE classification, which includes information about the velum, lateral walls of the oropharynx, tongue, and epiglottis [11]. This classification has been used by authors like Sher et al [12] and Sadaoka et al [13], who described it as easy to apply and reproduce. It also allows maneuvers such as manual closure of the mouth and the Esmarch maneuver by mandibular advancement [14].…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] For example, a prospective and controlled study14 which induced sleep with titrated doses of propafenone (propofolR) and evaluated UAW behavior in a group of patients with apnea showed that this method was safe, specific and sensitive. In our study we used a methodology similar to the one described by Sadaoka et al 27 and we induced sleep with low doses and slow dripping of midazolam, acting only as a sleep inducer and not as a sedative agent. We showed that the method is safe, and during the procedure the patients could wake up at any time.…”
Section: Discussionmentioning
confidence: 99%